Morphological, micro and macro nutrient analysis of the medicinal plant glory lily (Gloriosa superba L.) - P. Kabilar, P. Paneerselvam1, M. Gayathri2, S. Ravi1*, S. Ashokkumar, K. Mallika1 (Journal of Experimental Sciences, 2011)
In this study the three different treated tuber and seed samples of Glory lily were collected from farmer field's of Udayarpalayam and analyzed for the possible presence of colchicines using SEM technique. The results of SEM have shown that the presence of elements Ca and Fe are found only in Organic Manure Treatment. Also the quantitative estimation of EDX spectra observation confirms the percentage of Zn in Organic Manure Treatment (T3) was the highest among all the treatments. In conclusion from the results, Glory Lily may be considered as colchicines sources for the chemical constituents of medicine industry. Further it would be useful of producing high amount of colchicines for pest control based on natural products.